2018
DOI: 10.3390/en11123246
|View full text |Cite
|
Sign up to set email alerts
|

Kraft Lignin Grafted with Polyvinylpyrrolidone as a Novel Microbial Carrier in Biogas Production

Abstract: The objective of this study was to verify the effect of kraft lignin as a microbial carrier on biogas/methane yield. An anaerobic co-digestion test process was carried out, in which confectionery waste was used with sewage sludge. At the first stage of the study pure lignin and lignin combined with polyvinylpyrrolidone (PVP) were subjected to an extensive physicochemical analysis. Their morphology, dispersion and adsorption properties were determined. The two materials were also subjected to thermal, spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…The carrier was added to the mixture at an amount based on data in reference publications [32,33]. The authors of this study made partial physicochemical analysis of the lignin+PVP material in earlier tests [25,26], which showed that it met essential requirements for the microbial carrier in the AD process.…”
Section: Carrier Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…The carrier was added to the mixture at an amount based on data in reference publications [32,33]. The authors of this study made partial physicochemical analysis of the lignin+PVP material in earlier tests [25,26], which showed that it met essential requirements for the microbial carrier in the AD process.…”
Section: Carrier Preparationmentioning
confidence: 99%
“…The biogas efficiency for individual substrates was calculated by subtraction of the volume of biogas produced from the inoculum alone from the volume of biogas produced from the samples. The equation presented by the authors in earlier studies was used to calculate the cumulative amount of biogas generated from the inoculum (digested sewage sludge) in the bioreactors with a given substrate or mixture of substrates [25,26].…”
Section: Qualitative and Quantitative Analysis Of Biogasmentioning
confidence: 99%
See 3 more Smart Citations